Optimization of pullulanase production by Aspergillus flavus under solid-state fermentation. (February 2022) - Naik, Bindu; Goyal, S.K.; Tripathi, Abhishek Dutt; Kumar, Vijay
Abstract: Pullulanase is a promising candidate for industrial applications. But less yield and high cost limited its application. Hence, the present study aims to optimize nutrients for increasing the yield of fungal pullulanase to resolve these limitations. The findings of Plackett Burman Design showed that only 5 of 19 nutrients influenced the yield of pullulanase significantly. Box-Behnken Design (BBD) was implemented to establish the optimal concentration of the significant nutrients. After statistical optimization for KH2 PO4, yeast extract, peptone, and MnSO4, supplemented in the substrate wheat bran, the overall increase in yield was 1.63 fold. In all the flasks (500 to 5000 mL capacity containing 10–100 g dry substrate), almost the same yield has been produced (647.00 ± 25.139 U/gds) suggesting that the production of pullulanase can readily be scaled up under optimized conditions. This is the first nutrient optimization study of pullulanase production by Aspergillus flavus in solid state fermentation using wheat bran. Graphical abstract: Unlabelled Image Highlights: Plackett Burman Design results show that only 5 of 19 nutrients influenced the yield of pullulanase. Box-Behnken Design was used to establish the optimal concentration of the significant nutrients. Yeast extracts, peptone, KH2 PO4 and MnSO4 showed positive impact on the pullulanase yield. The maximum pullulanase activity of 648.0 U/gds was achieved with overall increase in 1.63 fold. First report of nutrient optimization for pullulanase production by Aspergillus flavus in SSF